Electronic Band Structure and Optical Properties of HgPS3 Crystal and Layers - de Simoni, Beatriz; Rybak, Miłosz; Antonatos, Nikolas; Herman, Artur P.; Ciesiołkiewicz, Karolina; Tołłoczko, Agata K.; Peter, Maciej; Piejko, Adrianna; Mosina, Kseniia; Sofer, Zdeněk; Kudrawiec, Robert (Journal of physical chemistry. C, 2024)
Transition metal thiophosphates (MPS3) are of great interest due to their layered structure and magnetic properties. Although HgPS3 may not exhibit magnetic properties, its uniqueness lies in its triclinic crystal structure and in the substantial mass of mercury, rendering it a compelling subject for exploration in terms of fundamental properties. In this work, we present comprehensive experimental and theoretical studies of the electronic band structure and optical properties for the HgPS3 crystal and mechanically exfoliated layers from a solid crystal. Based on absorption, reflectance and photoluminescence measurements supported by theoretical calculations, it is shown that the HgPS3 crystal has an indirect gap of 2.68 eV at room temperature. The direct gap is identified at the Γ point of the Brillouin zone (BZ) ≈ 50 meV above the indirect gap. The optical transition at the Γ point is forbidden due to selection rules, but the oscillator strength near the Γ point increases rapidly and therefore the direct optical transitions are visible in the reflectance spectra approximately at 60–120 meV above the absorption edge, across the temperature range of 40 to 300 K. The indirect nature of the bandgap and the selection rules for Γ point contribute to the absence of near-bandgap emission in HgPS3. Consequently, the photoluminescence spectrum is primarily governed by defect-related emission. The electronic band structure of HgPS3 undergoes significant changes when the crystal thickness is reduced to tri- and bilayers, resulting in a direct bandgap. Interestingly, in the monolayer regime, the fundamental transition is again indirect. The layered structure of the HgPS3 crystal was confirmed by scanning electron microscopy (SEM) and by mechanical exfoliation.